The correct answer to this is D
Answer:
Solution given:
m∠ADB=(4x−12)°
m∠CDB=(3x+6)°
m∠ADC =?
Since diagonal BD bisect the angle <ADC
so
m∠ADB= m∠ADC
(4x-12)°=(3x+6)°
4x-3x=6-12
x=12+6
x=18°
again.
<ADB=m∠ADB+ m∠ADC=4×18-12+3×18+6=120°
So
<u>the m∠</u><u>ADC</u><u> </u><u>=</u><u>1</u><u>2</u><u>0</u><u>°</u>
The first step is to divide by four to both sides
Answer:
Dollhouse Melanie Martinez
Step-by-step explanation:
Pemdas
ok if we look at the first one
exponents first
2^3=8
2^3=8
we have
4*8/8
4*8=32
32/8=4
das is answer
the first one is the answer